2015
DOI: 10.1371/journal.pone.0127335
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Practice of Fertility Preservation for Patients with Cancer

Abstract: Fertility is important to women and men with cancer. While options for fertility preservation (FP) are available, knowledge regarding the medical application of FP is lacking. Therefore we examined FP practices for cancer patients among reproductive endocrinologists (REs). A 36 item survey was sent to board-certified REs. 98% of respondents reported counseling women with cancer about FP options. Oocyte and embryo cryopreservation were universally offered by these providers, but variability was noted in reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This strategy of ovarian stimulation enables a follicular maturation while maintaining serum E 2 levels close to the normal ranges [5,18]. Therefore, COSTLES protocol now represents the preferred option for most of oncofertility specialists in case of estrogen-sensitive diseases [7,19], even though robust data to support an actual oncologic risk related to conventional stimulation protocol is lacking [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy of ovarian stimulation enables a follicular maturation while maintaining serum E 2 levels close to the normal ranges [5,18]. Therefore, COSTLES protocol now represents the preferred option for most of oncofertility specialists in case of estrogen-sensitive diseases [7,19], even though robust data to support an actual oncologic risk related to conventional stimulation protocol is lacking [20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, specific protocols have been developed, in order to combine multiple follicular growth throughout exogenous FSH administration, while limiting the effect of hyper-estradiolemia or maintaining serum E 2 levels within the normal ranges [5]. Hence, COS with anti-aromatase (AI) supplementation [6] is now largely used for BC patients seeking FP [7]. Nevertheless, few data have compared, in BC patients, the results obtained with conventional GnRH antagonist protocols and controlled ovarian stimulation with letrozole supplementation (COSTLES) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of a standardized program is known to enhance the application of existing recommendations and implementation of FP procedures before treatment start and/or before HSCT; such a program may also facilitate patients' decision making about FP. 9 The absence of an SOP significantly increases the risk of variability of practices 17 and could present a barrier to counseling. Ideally, in the FP process, the pediatric hematologist/oncologist, as a treating doctor, has a central role; this pivotal role requires the proper management of information with the patient and his/her family.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of the systematic review was to summarize the available evidence and encourage continued research on this important and timely topic. Dissemination of such information is critical as our group has demonstrated that fertility preservation practices are variable among Reproductive Endocrinologists [39]. Although the meta-analysis contains significant clinical and statistical heterogeneity, this method of quantitative analysis is reasonable when only observational data exists.…”
Section: Discussionmentioning
confidence: 99%
“…Dissemination of this information is important as application of fertility preservation strategies vary widely [39]. More work is needed before luteal phase starts are applied broadly in the general infertility population, but they do have potential in improving convenience of ART.…”
Section: Discussionmentioning
confidence: 99%